Influence of Real Earning Management on Subsequent Dividend Payout Decisions and Corporate Returns: A Case of Developing Economy - Ali, Shahid; Jiang, Junfeng; Murtaza, Ghulam; Khan, Muzammal (Frontiers in Environmental Science, 2022)
Real Earning Management (REM) enhances the control of managers on the financial reporting of firms. However, its influence on financial decisions in the coming years is not well documented, especially in developing countries. This study investigates the influence of three REM activities on subsequent years' dividend payout decisions (DPD) and annual corporate returns of firms listed on the Pakistan Stock Exchange (PSX). The study employed panel data from 2011-2020 of 120 large manufacturing firms to i) measure the extent of REM activities and ii) investigate the impact on future financial decisions of dividends and reported returns. This study used multiple proxies of return for robustness. Consistent with empirical studies, the REM negatively impacts the following years' returns. However, its effect on dividend payout policy is insignificant. This indicates that Pakistani firms are more concerned with smooth dividend payout to investors than coherent returns reporting. The study provides significant evidence from a developing economy and has implications for investors, analysts, and policymakers.